Toxoplasma gondii infection in farmed wild boars (Sus scrofa) in three cities of northeast China - Bai, Meng-Jie; Zou, Yang; Elsheikha, Hany M.; Ma, Jian-Gang; Zheng, Wen-Bin; Zhao, Quan; Zhang, Xiao-Xuan; Zhu, Xing-Quan (Mary Ann Liebert, 2017)
The apicomplexan protozoan parasite Toxoplasma gondii is a widely distributed etiological agent of foodborne illness. This parasite can cause production losses in livestock and serious disease in humans through consumption of contaminated meat. Pig meat is the most likely source of human infection, and wild boars may play a role in the transmission of T. gondii by serving as a reservoir host. This study aimed to investigate the seroprevalence of antibodies to T. gondii among farmed wild boars in China. In an 11-month survey, a total of 882 serum samples were obtained from farmed wild boars from three cities (Jilin City, Siping City, and Baishan City) in Jilin province, Northeast China and were tested for antibodies specific for T. gondii. Using modified agglutination test and a cutoff titer of 1:25, the prevalence of T. gondii infection in the examined samples was 10.0% (88 of 882). The highest seroprevalence was observed in animals from Jilin city (15.3%, 43/281) and followed by Siping (11.4%, 30/263) and Baishan (4.4%, 15/338). Logistic regression analysis revealed a significant correlation between the investigated geographic region and T. gondii infection. In addition, prevalence was higher in females compared to males, and the highest prevalence was detected in piglets. These findings indicate that farmed wild boars may become a source of foodborne toxoplasmosis, posing a food safety threat to the public health in the investigated areas. Implementation of effective measures to control T. gondii infection in farmed wild boars in China may be warranted.